2023
DOI: 10.1093/ageing/afac233
|View full text |Cite
|
Sign up to set email alerts
|

Listening to the patients’ voice: a conceptual framework of the walking experience

Abstract: Background walking is crucial for an active and healthy ageing, but the perspectives of individuals living with walking impairment are still poorly understood. Objectives to identify and synthesise evidence describing walking as experienced by adults living with mobility-impairing health conditions and to propose an empirical conceptual framework of walking experience. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Based on a recent expert consensus, physical mobility includes several domains that should be addressed, including gait volume, pace, cadence, asymmetry, gait phases, and gait variability [57]. This is also mirrored in a recent meta-ethnography of more than 120 qualitative studies summarizing patient perception of walking and mobility [58]. In this paper, patients largely agreed that aspects such as walking distance, perceived safety and balance concerns, and additional cognitive effort of walking are major features of walking capacity and affect walking activities, irrespective of their underlying conditions.…”
Section: Discussionmentioning
confidence: 98%
“…Based on a recent expert consensus, physical mobility includes several domains that should be addressed, including gait volume, pace, cadence, asymmetry, gait phases, and gait variability [57]. This is also mirrored in a recent meta-ethnography of more than 120 qualitative studies summarizing patient perception of walking and mobility [58]. In this paper, patients largely agreed that aspects such as walking distance, perceived safety and balance concerns, and additional cognitive effort of walking are major features of walking capacity and affect walking activities, irrespective of their underlying conditions.…”
Section: Discussionmentioning
confidence: 98%
“…Ownership for patient involvement should be across the consortium, and the identification of needs and expectations for the process should be undertaken early on with patient advisers. This approach has already demonstrated positive impact on the larger project and on study protocols, including articulating measurement concepts which form the basis of all study protocols and regulatory proceedings [58] and very high levels of acceptability for the digital technologies being explored in the project [59] .…”
Section: Progress and Remaining Barriers To Widespread Use Of Digital...mentioning
confidence: 99%
“…Increasing research has studied this parameter in healthy adults [ 11 14 ], and has shown that walking cadence decreases with age, with normative values for older adults ranging between <22 and >85 steps·min −1 (lower and uppermost quintiles, respectively) [ 13 ]. In COPD, individuals have reported “how fast they walk” as a meaningful aspect of their health [ 15 , 16 ] and, thus, research has recently started to measure cadence. Regrettably, walking cadence in COPD has to date only been assessed during limited periods of time [ 17 ] and under controlled conditions, i.e.…”
Section: Introductionmentioning
confidence: 99%